Corrigendum. (Journal of Interpersonal Violence, 2025)
The article focuses on the feasibility and acceptability of using experience sampling methods (ESM) with trauma-exposed sexual minority women (SMW). The study involved 161 participants who completed a baseline assessment and 14 days of daily surveys, with a high initiation rate of 94% and a completion rate of 45%. However, during follow-up research, suspicious behaviors indicative of bots or fraudulent responses were detected, leading to a rigorous validation process that resulted in the removal of invalid participants. The findings suggest that despite these challenges, the core themes of participant experiences remained consistent, highlighting the importance of robust bot-detection protocols and the need for careful participant verification in future research.